Sensing temperature with Tb-Eu-based luminescent thermometer: A novel approach to increase the sensitivity - Tcelykh, Liubov O.; Yu. Kozhevnikova, Vladislava; Goloveshkin, Alexander S.; Latipov, Egor V.; Gordeeva, Elena O.; Utochnikova, Valentina V. (Sensors and actuators. A. Physical., 2022)
To obtain ratiometric temperature sensor with high sensitivity we have synthesized three rows of bimetallic Tb-Eu hydroxybenzoates, whose sensitivity was expected to exceed the theoretical limit due to the presence of the temperature-dependent OH-quenching. Single crystals of two new bimetallic complexes were obtained, and their crystal structures were determined. Despite europium complexes with the selected ligands do not emit light, bimetallic Tb-Eu complexes with 3- and 4-hydroxybenzoates demonstrate europium luminescence with the quantum yield up to 77 %. Selected 3- and 4-hydroxybenzoates demonstrated temperature-dependent luminescence in the range of 25–100 °C. For 3-hydroxybenzoate of Tb-Eu, thermometer sensitivity reached 4 %/°C at 100 °C, which exceeds the expected limit of 3.3 %/°C at this temperature and is the highest reported value at this temperature. Temperature resolution is about 3 °C. [Display omitted] •Bimetallic Tb-Eu hydroxybenzoate formation increases europium luminescence efficiency from 0 % to up to 77 %.•Tb-Eu 3- and 4-hydroxybenzoates demonstrate temperature-dependent luminescence in the range of 25–100 °C.•The sensitivity reached 4 %/°C at 100 °C, which exceeds the theoretical limit.•Temperature resolution is about 3 °C.